Improving an existing proxy-based approach for floodplain denitrification assessment to facilitate decision making on restoration - Kaden, Ute Susanne; Schulz-Zunkel, Christiane; Fuchs, Elmar; Horchler, Peter; Kasperidus, Hans Dieter; de Moraes Bonilha, Otavio; Rupp, Holger; Tschikof, Martin; Weigelhofer, Gabriele; Hein, Thomas; Scholz, Mathias (The Science of the total environment, 2023)
Excess nitrogen (N) from agricultural sources is a major contributor to the water pollution of rivers in Europe. Floodplains are of tremendous importance as they can permanently remove nitrate (NO3) from the environment by releasing reactive N to the atmosphere in its gaseous forms (N2O, N2) during denitrification. However, the quantitative assessment of this ecosystem function is still challenging, particularly on the national level. In this study, we modeled the potential of NO3-N removal through microbial denitrification in soils of the active floodplains of the river Elbe and river Rhine in Germany. We combined laboratory measurements of soil denitrification potentials with straightforward modelling data, covering the average inundation duration from six study areas, to improve an existing Germany-wide proxy-based approach (PBAe) on NO3-N retention potential. The PBAe estimates this potential to be 30–150 kg NO3-N ha−1 yr−1. However, with soil pH and Floodplain Status Category identified as essential parameters for the proxies, the improved PBA (PBAi) yields a removal potential of 5–480 kg N ha−1 yr−1. To account for these parameters, we applied scaling factors using a bonus-malus system with a base value of 10–120 N ha−1 yr−1. Upscaling the determined proxies of the PBAi to the entire active floodplains of the river Elbe and river Rhine results in similarly high NO3-N retention sums of ~7000 t yr−1 in spite of very different retention area sizes, strengthening the argument for area availability as the primary objective of restoration efforts. Although PBAs are always subject to uncertainty, the PBAi enables a more differentiated spatial quantification of denitrification because local key controlling parameters are included. Hence, the PBAi is an innovative and robust approach to quantify denitrification in floodplain soils, supporting a better assessment of ecosystem services for decision-making on floodplain restoration. [Display omitted] •A robust nitrate removal estimate denitrification in large floodplains•Linking measurements with a flooding model for improved NO3-N removal proxies•Active floodplains of Elbe and Rhine are both capable of removing ~7000 t NO3-N yr−1.•Improved proxy-based approach for decision-making on floodplain restoration